2019
DOI: 10.1088/1757-899x/579/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing the Sulfur Content of Crude Oil by Ultra-Sound and Activated Carbon Assisted Oxidative Method

Abstract: There is a large amount of sulfur compound in crude oil, sulfur gases such us H2S for example are emitted and can affect the environment and finally can cause problems during the processing operation of crude oil. Therefore, in this study, a method for the removal of sulfur from crude oil using an ultrasound device has been proposed. This method is a combination of oxidative method and applying ultrasonic waves to achieve the allowable sulfur content in crude oil. Samples of crude oil have been taken that we g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Khlaif and Bded [97] carried out the ODS (followed by extraction) of crude oil containing 1.95% total S by weight in the presence of US and AC using different volumes of acetic acid and 50 wt% H 2 O 2 . As a result of the increase of the amount of AC used from 3 to 9 g, the number of active sites in AC increased, thus improving ODS and an optimum desulfurization of 81.325% was obtained by using 9 g AC, 40 mL H 2 O 2 , 30 mL acetic acid at 50 °C.…”
Section: Types Of Catalysts In Uaodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Khlaif and Bded [97] carried out the ODS (followed by extraction) of crude oil containing 1.95% total S by weight in the presence of US and AC using different volumes of acetic acid and 50 wt% H 2 O 2 . As a result of the increase of the amount of AC used from 3 to 9 g, the number of active sites in AC increased, thus improving ODS and an optimum desulfurization of 81.325% was obtained by using 9 g AC, 40 mL H 2 O 2 , 30 mL acetic acid at 50 °C.…”
Section: Types Of Catalysts In Uaodsmentioning
confidence: 99%
“…In addition, acetic acid is relatively low-cost [176] . In studies [97] , [165] , [177] in which desulfurization of crude oil, coal and model diesel fuel with the help of US by using acetic acid-HP oxidant system was performed, it was indicated that high desulfurization efficiency is reached in a short time at relatively low temperatures. The oxidation of sulfur compounds is caused by peroxyacetic acid and hydroxyl radicals formed in situ in the aqueous phase.…”
Section: Types Of Catalysts In Uaodsmentioning
confidence: 99%
See 1 more Smart Citation